Inflammatory Marker and Sociodemographic Profile of Type 2 Diabetes Mellitus Patients (Medicine Today, 2026)
Introduction with Objective: To evaluate the inflammatory marker and sociodemographic profile of type 2 diabetes mellitus patients. Methods: This study was a hospital based cross sectional study conducted at the department of Biochemistry of BIRDEM academy from January 2023 to December 2023. Purposive sampling was done according to availability of patients. Ethical clearance was obtained from the appropriate authority to get permission to collect data. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) Results: mean age of the patients was 46.2±9.38 years. In our study, most of the patients were male (n=75, 51%). 77 patients (52%) had the family history of diabetes mellitus. 52.0% of patients were smokers, and 48.7% of patients consumed alcohol. Only 25.0% of patients engaged in physical activity. The majority of patients (31%) were moderately active in our study, while 25% of patients were inactive. Ischaemic heart disease was the most commonly associated disease (57%) with DM. GGT level was 41.94±26.35 u/L and hsCRP level was 4.41±11.08 mg/L of the study population. Conclusions: High levels of pro-inflammatory cytokines and hs-CRP are strongly associated with chronic inflammation and oxidative stress in the pathogenesis of T2DM.Medicine Today 2026, Vol.38 (1): 90-92